Plan de negocios para la implementación de un comedor infantil en el restaurante "El Balcón de la Riobambeñita" ubicado en la parroquia Guayllabamba - Almache Cadena, María José (2012)
The business idea was the creation of a child as part dining restaurant attached to “El Balcón de la Riobambeñita”. In chapter one describes the emergence of the idea of the business, whose overall objective was: to develop a business plan to determine the feasibility of conducting market research, marketing and finance that enables the implementation of a child in the restaurant dining “El Balcón de la Riobambeñita”. In chapter two we investigated and analyzed the environment where they deciphered the hotel and restaurant industry, maintains an annual average economic growth of 3.90% over the period 2006 to 2012. We also examined the environmental variables and the position of the business with respect to the competitive forces of Porter. In organizational distribution company is decrypted, its vision, mission, objectives and goals, the value chain, the market entry strategies and growth. Environment was made after the market research, the results were positive for the market inquiries, consumers and competition, generating business opportunity which allowed developing the marketing plan and organizational structure of the company. Chapter four concerns the introduction of the service to the market, with the positioning strategies: differentiation based on service characteristics, as it will be the only place in the parish of Guayllabamba which will feature a soup kitchen. The advertising budget was made in relation to the costs to be incurred by the company. We also performed a sales projection for five years taking into account the percentage of restaurant sales performance “El Balcón de la Riobambeñita”. Finally gave financial evaluation returning favorable investment results unfunded plan a 24,66%, 41,31% and 60,55%, while return on a fund it 30,20%, 52,15% and 78,01% in scenarios: pessimistic, optimistic and expected respectively. It is concluded and recommended that the business is viable and should be carried out.